Transcriptome Dynamics of the Inflorescence in Reciprocally Formed Allopolyploid Tragopogon miscellus (Asteraceae) - Shan, Shengchen; Boatwright, J. Lucas; Liu, Xiaoxian; Chanderbali, Andre S.; Fu, Chaonan; Soltis, Pamela S.; Soltis, Douglas E. (Frontiers in Genetics, 2020)
Polyploidy is an important evolutionary mechanism and is prevalent among land plants. Most polyploid species examined have multiple origins, which provide genetic diversity and may enhance the success of polyploids. In some polyploids, recurrent origins can result from reciprocal crosses between the same diploid progenitors. Although great progress has been made in understanding the genetic consequences of polyploidy, the genetic implications of reciprocal polyploidization remain poorly understood, especially in natural polyploids. Tragopogon (Asteraceae) has become an evolutionary model system for studies of recent and recurrent polyploidy. Allotetraploid T. miscellus has formed reciprocally in nature with resultant distinctive floral and inflorescence morphologies (i.e., short- vs. long-liguled forms). In this study, we performed comparative inflorescence transcriptome analyses of reciprocally formed T. miscellus and its diploid parents, T. dubius and T. pratensis. In both forms of T. miscellus, homeolog expression of ~70% of the loci showed vertical transmission of the parental expression patterns (i.e., parental legacy), and ~20% of the loci showed biased homeolog expression, which was unbalanced toward T. pratensis. However, 17.9% of orthologous pairs showed different homeolog expression patterns between the two forms of T. miscellus. No clear effect of cytonuclear interaction on biased expression of the maternal homeolog was found. In terms of the total expression level of the homeologs studied, 22.6% and 16.2% of the loci displayed nonadditive expression in short- and long-liguled T. miscellus, respectively. Unbalanced expression level dominance toward T. pratensis was observed in both forms of T. miscellus. Significantly, genes annotated as being involved in pectin catabolic processes were highly expressed in long-liguled T. miscellus relative to the short-liguled form, and the majority of these differentially expressed genes were transgressively down-regulated in short-liguled T. miscellus. Given the known role of these genes in cell expansion, they may play a role in the differing floral and inflorescence morphologies of the two forms. In summary, the overall inflorescence transcriptome profiles are highly similar between reciprocal origins of T. miscellus. However, the dynamic homeolog-specific expression and nonadditive expression patterns observed in T. miscellus emphasize the importance of reciprocal origins in promoting the genetic diversity of polyploids.